Plant-derived saccharides and their inhibitory potential on metastasis associated cellular processes of pancreatic ductal adenocarcinoma cells. (April 2020) - Schöll-Naderer, Meike; Helm, Ole; Spencker, Josephine; Pfeifer, Lukas; Rätsch, Tilo; Sebens, Susanne; Classen, Birgit
Abstract: This study intends to investigate the inhibitory potential of different plant derived saccharides on cell migration and adhesion of pancreatic ductal adenocarcinoma (PDAC) cells to microvascular liver endothelium, particularly considering the role of transmembranous galectin-3. PDAC cell lines PancTu1 and Panc1 were characterized by considerable (transmembranous) galectin-3 (Gal3) expression. SiRNA mediated Gal3 knockdown as well as treatment with differentially processed pectins and arabinogalactan-proteins (AGPs) did not impact on cell migration of either PDAC cell line. In contrast, Gal3 knockdown reduced adhesion of PDAC cells to the liver endothelial cell line TMNK-1 being more pronounced in Panc1 cells. Similarly, plant derived substances did not impact cell adhesion of PancTu1 cells while partially hydrolyzed citrus pectin (MCP), pectinase-treated MCP (MCPPec ) and partially hydrolized AGP (AGPTFA ) clearly diminished adhesive properties of Panc1 cells. MCPPec or AGPTFA could not further intensify the adhesion reducing effect of galectin-3 knockdown, indicating that these plant derived polysaccharides are able to inhibit PDAC cell adhesion to liver endothelial cells in a galectin-3 dependent manner. Overall, these data suggest an inhibitory potential of plant derived processed saccharides which have undergone chemical modification in impairing PDAC cell adhesion to liver endothelium. Graphical abstract: Image 1 Highlights: An in vitro testsystem for adhesion of pancreatic ductal adenocarcinoma (PDAC) to liver cells has been developed. The role of transmembranous galectin-3 on this process is in the focus of this work. SiRNA mediated Gal3 knockdown reduced adhesion of PDAC cells to the liver cell line TMNK-1. Modified plant galactans clearly diminished adhesive properties of PDAC cells. Overall, these data suggest an inhibitory potential of plant derived processed galactans on metastasis.